2005
DOI: 10.1074/jbc.m505644200
|View full text |Cite
|
Sign up to set email alerts
|

A Role for the Distal Carboxyl Tails in Generating the Novel Pharmacology and G Protein Activation Profile of μ and δ Opioid Receptor Hetero-oligomers

Abstract: Opioid receptor pharmacology in vivo has predicted a greater number of receptor subtypes than explained by the profiles of the three cloned opioid receptors, and the functional dependence of the receptors on each other shown in gene-deleted animal models remains unexplained. One mechanism for such findings is the generation of novel signaling complexes by receptor hetero-oligomerization, which we previously showed results in significantly different pharmacology for and ␦ receptor hetero-oligomers compared with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
93
0
3

Year Published

2006
2006
2013
2013

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(102 citation statements)
references
References 33 publications
6
93
0
3
Order By: Relevance
“…7 In recent years, several studies have shown that and ␦ receptors form functionally distinct heterodimeric or hetero-oligomeric complexes. [8][9][10][11] The physiological and pharmacological signifi cance of -␦ interactions have been substantiated by recent studies using opioid receptor gene knockout animals. 12 The existence of intermodulatory effects between and ␦ receptors has spawned a new interest in the pursuit of ligands with a mixed interaction profi le at the and ␦ receptors as a novel therapeutic approach for the treatment of pain.…”
mentioning
confidence: 99%
“…7 In recent years, several studies have shown that and ␦ receptors form functionally distinct heterodimeric or hetero-oligomeric complexes. [8][9][10][11] The physiological and pharmacological signifi cance of -␦ interactions have been substantiated by recent studies using opioid receptor gene knockout animals. 12 The existence of intermodulatory effects between and ␦ receptors has spawned a new interest in the pursuit of ligands with a mixed interaction profi le at the and ␦ receptors as a novel therapeutic approach for the treatment of pain.…”
mentioning
confidence: 99%
“…Most importantly, the ability of SSTR4 to form homodimer was not observed with the C-tail of SSTR1 [106]. The specificity of the C-tail in the process of dimerization is not restricted to SSTR subtypes only but was also described for δ-opioid receptor-trafficking and heterodimerization of GABABR subtypes GABABR1 and GABABR2 [34,37], and for μ-and δ-opioid receptor (ORs) heterodimerization [121]. SSTR1/SSTR5 heterodimerization leads to greater efficiency in signaling and inhibition of adenylate cyclase and cAMP synthesis [65].…”
Section: Receptorsmentioning
confidence: 92%
“…Les propriétés pharmacologiques et signalétiques des récepteurs opiacés peuvent en effet varier en fonction du profil d'expression protéique qui est spécifique à chaque type cellulaire. Différents partenaires de dimérisation peuvent ainsi modifier les propriétés pharmacologiques des récepteurs [24,25]. Pourtant, si aucune inversion de l'ordre d'efficacité et/ou de puissance des ligands n'est observée, ces modifications ne constituent pas une preuve irréfutable de la présence de conformations actives spécifiques aux ligands.…”
Section: Sélectivité Fonctionnelle Et Signalisation Des Récepteurs Opunclassified
“…Pourtant, si aucune inversion de l'ordre d'efficacité et/ou de puissance des ligands n'est observée, ces modifications ne constituent pas une preuve irréfutable de la présence de conformations actives spécifiques aux ligands. L'hétérodimérisation DOR/MOR, par exemple, produit un changement de couplage du DOR de Gi3 vers Gz, mais le DPDPE reste plus efficace que la deltorphine II pour activer les différentes sous-unités G [25]. Par ailleurs, la sélectivité fonctionnelle ne se limite pas à produire l'activation de différentes sous-unités G.…”
Section: Sélectivité Fonctionnelle Et Signalisation Des Récepteurs Opunclassified